Pelaksanaan Tradisi Khatam Quran serta Implikasi terhadap Akhlak Murid Madrasah Diniyah Takmiliyah Awaliyah - Susilawati Susilawati; Afnibar Afnibar; Juliana Batubara (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Bukittinggi has a cultural style that is known for its Islamic traditions, making this area an area that has a high Islamic heritage. It is not uncommon for local, national and even international researchers to conduct research in this area to determine the development of Islamic values. One of them is the Khatam Qur'an tradition which has developed in almost all areas in Bukittinggi, one of which is in the Campago Guguak Bulek sub-district. This tradition of khatam Qur'an is carried out after Eid, when children are able to memorize the Qur'an. As an Islamic cultural heritage that has been passed down from generation to generation, this tradition has become a routine agenda for the people around the Bukittinggi area and is carried out with great fanfare. In this article, we will explore the extent to which the Khatam Qur'an tradition is able to shape children's morals towards social life in the Campago Guguak Bulek sub-district. This research is qualitative research, because the research object is social interaction. This kind of interaction can only be explained by interviewing and observing the social interaction to find clear relationship patterns. The social interaction referred to by researchers here is the Khatam Qur'an tradition in Campago Guguak Bulek Village, Bukittinggi City.